Rozner, Sarah (audio interview #2 of 20) - Rozner, Sarah (b. 1892 - d.12/?/1980); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the first interview with Sarah Rozner conducted in her home. Rozner manages by herself fairly well, using a cane to walk, but has some breathing difficulties after exertion. She seemed rather vigorous and her voice and manner of speaking was very strong and rather tough. Rozner still has a heavy accent; additionally, she has a habit of taking long pauses in between sentences and a tendency to jump from one subject to another with very little chronology to her activities. TOPICS - family background; immigration; work; union activities; treatment of women in the union; Chicago strikes of 1910 and 1915;activities as a Business Agent; feminist consciousness; development of political consciousness; Brookwood Labor College; factional struggle in ACWA; 3/27/1973